Comparative Analysis of Three Preloaded and One Manual Injector for Intraocular Lens Implantation - K. B. Pershin; N. F. Pashinova; A. Yu. Tsygankov; I. V. Kosova; O. S. Saidalieva (Oftalʹmologiâ, 2023)
Purpose: to evaluate the incision width and implantation time of different IOL models using three preloaded and one manual injector. Patients and methods. 146 patients (160 eyes) including 94 females and 52 males were included in a prospective study. Group I — Isert® (28 patients, 32 eyes); Group II — Multisert® (27 patients, 30 eyes); Group III — Autonome® (45 patients, 50 eyes) and Group IV — Monarch® (46 patients, 48 eyes). mean age of patients was 71.8 ± 11.7 years, follow-up period — 3.0 ± 0.2 months. Results. There were no significant differences (p > 0.05) between the groups when comparing the incision width before IOL implantation. After lens implantation, the incision width in group I was significantly higher than in groups II (p = 0.04), III (p = 0.037) and IV (p = 0.029). There were no significant differences in incision width after IOL implantation between groups II, III, and IV (p > 0.05). The average increase in corneal incision width in group I was 0.6 mm, and for groups II, III, and IV it ranged from 0.2 to 0.3 mm. Groups II, III, and IV showed lower values of surgically induced astigmatism compared with group I (0.47 ± 0.06 D, 0.41 ± 0.06 D, and 0.44 ± 0.07 D compared with 1.12 ± 0.17 D, respectively; p < 0.05 for all groups). No significant differences were found between groups II, III, and IV. Minimum implantation time was observed for groups II and III, maximum for groups I and IV, with a mean difference of about 30 seconds. Differences when comparing the mean IOL implantation time were not statistically significant (p > 0.05). Conclusion. This paper presents the first worldwide comparative analysis of four IOL implantation systems, including Isert®, Multisert®, Autonome®, and Monarch®. The new Multisert® IOL implantation system has similar advantages to the known monofocal IOL injectors with respect to corneal incision width, surgically induced astigmatism magnitude, and time required for IOL implantation. IOL implantation time did not depend on the type of implantation (hydro- or viscous) and the type of injector.